Mutations altering the cellular localization of the phage lambda receptor, an Escherichia coli outer membrane protein. - Emr, S D (1978)
Two mutant strains of Escherichia coli have been isolated in which the cellular location of an outer membrane protein, the phage lambda receptor (the lamB gene product), is altered. These mutations were initially selected in a strain containing a lamB-lacZ fusion. In the parent strain the protein coded for by the hybrid gene is located, at least in part, in the outer membrane. In the mutants it is located in the cytoplasm. The mutations responsible for the alteration of cellular location lie very early in the lamB gene, in a region corresponding to the NH2-terminus of the lambda receptor protein. One of these mutations is a small deletion internal to the lamB gene. When this mutation is present in an otherwise wild-type lamB gene, the protein produced is of lower molecular weight than normal receptor. The other mutation behaves as a point mutation; when it is present in an otherwise normal lamB gene, reversion can be demonstrated. The molecular weight of this mutant protein, which is located in the cytoplasm, is larger than that of the wild-type gene product by approximately 2000. It is suggested that these two mutations are in the portion of the lamB gene coding for a signal sequence and thereby block export of the protein.